PENGARUH STRES KERJA, BUDAYA KERJA DAN KEPUASAN KERJA TERHADAP LOYALITAS KERJA KARYAWAN KOPINAN 24 PATI - Wijaya, Bagus; Kiswoyo, Kiswoyo (Politeknik Negeri Ambon, 2025)
Introduction: This research aims to explore the influence of work stress, work culture, and job satisfaction on employee loyalty at Kopinan 24 Pati. The population studied consists of Generation Z employees working at Kopinan 24 Pati, totaling 40 individuals. Methods: The research sample was taken using a census sampling method, which included the entire population in the sample, resulting in 40 respondents. Data analysis was conducted using multiple linear regression methods. Results: The results indicate that work stress does not affect employee loyalty. In contrast, work culture and job satisfaction were found to have a significant impact on employee loyalty at Kopinan 24 Pati. These findings underscore the significance of internal management and its underlying factors in shaping employee loyalty at Kopinan 24 Pati. Research Recommendations for the Company, although work stress does not affect the work loyalty of Generation Z employees at Kopinan 24 Pati, the company still needs to pay attention to factors that may cause stress. The company can implement stress management programs and provide psychological support, such as counseling, related to employee issues that may be affecting performance. Establishing good communication between employees and supervisors, involving all employees in decision-making, and organizing social activities such as picnics when monthly targets are met are also ways to minimize work stress. These efforts can help create a healthier work environment and increase the work loyalty of Generation Z employees. The company is advised to strengthen an inclusive and collaborative work culture, as well as improve employee job satisfaction. This can be done through regular surveys and quarterly gatherings to understand employee needs, providing career development opportunities, giving rewards or appreciation to high-performing employees, and encouraging employee involvement in decision-making both at Kopinan 24 Pati and its branches in other cities. By implementing such a work culture, it is expected to create a supportive work environment and enhance the loyalty of Generation Z employees. Keywords: Work Stress, Work Culture, Job Satisfaction, Employee Loyalty